Nilai-nilai Pendidikan Dalam Petatah Petitih Adat Minangkabau (Alternatif Membangun Pendidikan Berkarakter) - Miswar Munir (Alhurriyah, 2013)
Minangkabau community who inhabited in west sumatera is known with "adat basandi syara', syara' basandi Kitabullah" as the foundation and outlook on life. To educate the young generation to understand and appreciate the principles of the tradition, there is a habit of the people who hold a petatah petitih activities in which there would be some basic principles of life, both individually and collectively are expected to establish the character of each of the next generation of Minangkabau community in accordance with their customs basis.